Diagnosis of Cyclic Vomiting - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
In a study at Children's Hospital, Ann Arbor, MI, and Children's Memorial Hospital, Chicago, designed primarily to compare cost-effectiveness of three methods of management of cyclic vomiting cases, one group of patients received an extensive diagnostic evaluation, a second was treated with empiric antimigraine drugs for 2 months, and a third an upper GI series with small-bowel follow-through (UGI-SBFT) plus empiric therapy.